Buscando un cónyuge: matrimonio, herencia y ayuda mutua en un distrito del Valle de Colca - Paerregaard, Karsten (Pontificia Universidad Católica del Perú. Fondo Editorial, 1990)
The purpose of my article is to contribute to the development of a general model of the social organization of the Andean world, in which few have been interested in the last ten years. There are two aspects that I am going to analyze based on data collected in the Tapay district, in the Colca valley, Cailloma province, Arequipa department. First, I want to analyze the marriage pattern that characterizes on the one hand the relationship between the Tapay district and the external world, and on the other hand the relationships between the social and cultural groups that make up the Tapay population. In other words, to analyze how exogamy and endogamy are manifested in the different levels of the society of Tapay. Secondly, I will try to interpret this marriage pattern within a broader context, that of Tapay's social organization. Therefore, I will present a series of data about the inheritance system and the mutual aid amongst the people of Tapay.

La finalidad de mi artículo es contribuir al desarrollo de un modelo general de la organización social del mundo andino, en el cual pocos se han interesado en los últimos diez años. Dos son los aspectos que voy a analizar en base a datos recogidos en el distrito de Tapay, en el valle de Colca, provincia de Cailloma, departamento de Arequipa. Primero, quiero analizar el patrón matrimonial que caracteriza por un lado la relación entre el distrito de Tapay y el rnundo externo, y por otro lado las relaciones entre los grupos sociales y culturales que forman la población de Tapay. En otras palabras, analizar cómo la exogamia y la endogamia se manifiestan en los diferentes niveles de la sociedad tapeña. Segundo, intentaré interpretar este patrón matrimonial dentro de un contexto más amplio, el de la organización social de Tapay. Por lo tanto, presentaré una serie de datos en torno al sistema de herencia en Tapay y la ayuda mutua entre los tapeños.
Looking for a spouse: marriage, inheritance and mutual aid in a Colca Valley district
Keywords: Antropología; https://purl.org/pe-repo/ocde/ford#5.04.03